2010
DOI: 10.1177/0022034510369460
|View full text |Cite
|
Sign up to set email alerts
|

Caries Inhibition by and Safety of Lactobacillus paracasei DSMZ16671

Abstract: Lactobacillus paracasei DSMZ16671, even if heat-killed, sensitively co-aggregates mutans streptococci specifically. Mutans streptococci are strongly implicated in caries induction in humans and rodents. We hypothesized: (1) that S. mutans recoveries from rats' teeth in vivo will decrease, with an associated decrease in caries, if these lactobacilli are fed to rats in an established caries model; and (2) that toxicological assays of these lactobacilli will show them to be benign. Four groups of specific-pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 20 publications
2
27
0
Order By: Relevance
“…However, probiotic therapy to prevent or combat oral disease is just evolving, and for example heat-killed bacteria were proven safe, with promising results in animal experiments [Tanzer et al, 2010].…”
Section: Discussionmentioning
confidence: 99%
“…However, probiotic therapy to prevent or combat oral disease is just evolving, and for example heat-killed bacteria were proven safe, with promising results in animal experiments [Tanzer et al, 2010].…”
Section: Discussionmentioning
confidence: 99%
“…The possible effect on MS when DNA but not live bacteria was detected is not clear but may be an effect of immune modulation, indicating that non-viable components of probiotic strains can have an influence on the oral microbiota [Taverniti and Guglielmetti, 2011]. Tanzer et al [2010] reported that heat-killed L. paracasei DSMZ16671 sensitively co-aggregated specifically with MS and inhibited colonisation of rat teeth by Streptococcus mutans 10449S, even though the animals were fed with a high-sucrose cariogenic diet. Interestingly, in an in vitro model using the same L. reuteri strains as the present study, alterations in the plaque ecosystem were demonstrated, and L. reuteri persisted and potentially integrated into mature dental biofilms for at least 20 days after cessation of dosing [Madhwani and McBain, 2011], in agreement with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial coaggregation could provide an explanation for the effect of probiotic bacteria on caries reduction Lang et al, 2010;Tanzer et al, 2010;Holz et al, 2013]. Although coaggregation between LB and SM was tested in our study, no signs of interaction between the species could be detected.…”
Section: Discussionmentioning
confidence: 57%
“…Thus, the tissue composition could determine the differential effect of probiotics relative to the local conditions around the lesions (saturation of the biofilm fluid). An alternative approach for those cases is the use of heat-killed or heatinactivated bacteria, which has demonstrated promising results [Holz et al, 2013;Tanzer et al, 2010].…”
Section: Discussionmentioning
confidence: 99%